Advanced introduction to sustainable tourism - Weaver, David B. (David Bruce) (Elgar advanced introductions., 2020)
This critical review of sustainable tourism, from its beginnings in the late 1980s to the present, examines the pressing challenges posed by the effects of global warming and the persistence of deep poverty and social unrest in many regions. David Weaver explores the convergence of mass and 'alternative' tourism as a dominant theme. Originally perceived as two incompatible forms of tourism, they are positioned in this book through enlightened mass tourism as unified components of a single global 'tourisystem' with the power to achieve sustainable tourism.